2018
DOI: 10.1152/japplphysiol.00911.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response to prescribed detraining among recreational athletes

Abstract: Exercise-induced cardiac remodeling (EICR) and the attendant myocardial adaptations characteristic of the athlete's heart may regress during periods of exercise reduction or abstinence. The time course and mechanisms underlying this reverse remodeling, specifically the impact of concomitant plasma volume (PV) contraction on cardiac chamber size, remain incompletely understood. We therefore studied recreational runners ( n = 21, age 34 ± 7 yr; 48% male) who completed an 18-wk training program (~7 h/wk) culminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
4
31
0
1
Order By: Relevance
“…4 Pedlar et al performed echocardiography in amateur runners after an 18 week training 5 programme and then after 4 and 8 weeks when participants were limited to <2 hours of training 6 a week. 27 Similarly to our findings they reported a 10.4% reduction in LV mass after 4 weeks 7 with no change in LV EDV even 8 weeks post-race. 8…”
Section: Effects Of Detraining On Cardiac Morphologysupporting
confidence: 89%
“…4 Pedlar et al performed echocardiography in amateur runners after an 18 week training 5 programme and then after 4 and 8 weeks when participants were limited to <2 hours of training 6 a week. 27 Similarly to our findings they reported a 10.4% reduction in LV mass after 4 weeks 7 with no change in LV EDV even 8 weeks post-race. 8…”
Section: Effects Of Detraining On Cardiac Morphologysupporting
confidence: 89%
“…In line with this, impairments in maximal cardiac output (Q max ) have been found after 12 days of inactivity due to a 10% decrement in exercise stroke volume and 4% increment in maximal heart rate (Coyle et al, 1984 ). Similar results have also been observed following a period of training cessation and head-down tilt bed rest during both maximal (Coyle et al, 1984 ; Pedlar et al, 2018 ) and submaximal exercise (Coyle et al, 1986 ; Capelli et al, 2008 ). Such reductions in Q max are critical as they may highly contribute in declining the maximal oxygen delivery capacity.…”
Section: Potential Morphological Physiological and Functional Changesupporting
confidence: 73%
“…For example, it has been found that expansions in blood volume can partially reestablish VO 2max losses following a period of training cessation; nonetheless, this manipulation was not able to compensate for endurance performance decrements (Coyle et al, 1986 ). Moreover, 4 weeks of training cessation have been shown to decrease performance during a time to exhaustion test (TTE) without affecting VO 2max in well-trained endurance athletes (Madsen et al, 1993 ; Pedlar et al, 2018 ). Impairments in endurance performance have also been found during 12–35 days of training cessation in both running and cycling incremental tests (Coyle et al, 1986 ; Houmard et al, 1992 , 1993 ), a Yo-Yo intermittent-test (Joo, 2018 ), a 3,000-m running time trial (Pereira et al, 2016 ) and a cycling TTE (Madsen et al, 1993 ).…”
Section: Potential Morphological Physiological and Functional Changementioning
confidence: 99%
See 1 more Smart Citation
“…46,47,48 Such persistent remodelling has also been reported in individuals undertaking temporary endurance training. 49,50,51 Group 3 represents the cohort with the least favourable adaptive response to pregnancy. These women have failed the 'cardiovascular screening test' in their previous pregnancies and may have an underlying cardiovascular deficit, causing a failure in adaptation in situations of circulatory stress.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%